Policing repeat and high-risk family violence: police and service-sector perceptions of a coordinated model. (15th January 2021) - Hamilton, Gemma; Harris, Lisa; Powell, Anastasia
ABSTRACT: Family violence forms a significant part of police-work, with many police agencies adopting evolving responses to family violence over time. This article presents the qualitative findings of a mixed-method evaluation of 'Alexis', a coordinated police-social-services approach to family violence piloted in the state of Victoria, Australia. In-depth interviews were conducted with 14 stakeholders (7 police members and 7 community service providers) to examine perceptions of how the model was working and how it differed from other policing approaches to family violence. Five key themes were extracted from the data via thematic analysis: (i) collaboration between police, an embedded family violence worker and other agencies; (ii) increased police accountability; (iii) adoption of a proactive major crime approach; (iv) emphasis on professional development; and (v) the allocation of dedicated time and resources. Implications for future policy development are discussed, with the findings highlighting promising practices for policing high-risk and recidivist family violence.